SOSIALISASI PANCASILA SILA KE-1 DENGAN MENGAJARKAN BACAAN SHOLAT DAN PRINSIP DASAR RUKUN ISLAM DAN RUKUN IMAN PADA SISWA SISWI SD JUARA JAKARTA UTARA UTARA - Yoka Mai Patra; Ana Chaerunisyah; Firdaus Suwarta; Ferena Athfannisa; Hidayat Hidayat (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Pancasila, as the foundation of the Indonesian state, emphasizes the importance of implementing moral and ethical values in societal life. One of the highly relevant values to highlight is the First Principle, "Belief in the One and Only God." Socializing the application of Pancasila's values, particularly the First Principle, poses a challenge that needs to be overcome in the digital and globalized era, especially for the younger generation. The generation familiar with technological advancements can be directed to understand and apply the First Principle in their daily lives. Socialization is conducted through engaging direct approaches. The results of the socialization, in the context of applying the values of the First Principle, involve guiding children to comprehend the significance of belief in the Almighty in their daily lives. By exploring the understanding of religious values, particularly through teaching prayers and the basic principles of Islamic beliefs and practices, they can develop an awareness of the existence of God and strengthen their spiritual values. The application of the First Principle enriches not only the religious dimension but also fosters attitudes of respect, tolerance, and harmony among individuals amidst cultural and belief diversity. Through direct interactions and engaging approaches, the younger generation can more easily internalize these values, bringing positive impacts in shaping their characters and considering the First Principle as a guide in facing the dynamics of modern life